2021
DOI: 10.1108/bfj-04-2021-0410
|View full text |Cite
|
Sign up to set email alerts
|

Food tourism: opportunities for SMEs through diaspora marketing?

Abstract: PurposeThe aim of this paper is to investigate the impact of the diaspora effect on food tourism. Focussing on the nexus of diaspora marketing, entrepreneurship and food tourism, this paper seeks to explore opportunities for food and drink small and medium-sized enterprises (SMEs) to engage in food tourism activities through diaspora marketing.Design/methodology/approachAs an investigation of an under-researched concept, this research uses mixed methods to develop a deeper understanding of diaspora effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In addition, based on the interdisciplinary perspective, scholars have also conducted analysis, directly combining communication science with e-commerce to form a new research model [12]. Bowen, based on the Egyptian scope, conducted a study on the impact of information systems as a dependent variable on the tourism industry, and the results show that the use of market information systems can help tourism enterprises improve the quality of their services [13]. Ashaari analyzed the tourism marketing service model based on web2.0 when analyzing tourism enterprises.…”
Section: E Relationship Between Tourism Marketing and Newmentioning
confidence: 99%
“…In addition, based on the interdisciplinary perspective, scholars have also conducted analysis, directly combining communication science with e-commerce to form a new research model [12]. Bowen, based on the Egyptian scope, conducted a study on the impact of information systems as a dependent variable on the tourism industry, and the results show that the use of market information systems can help tourism enterprises improve the quality of their services [13]. Ashaari analyzed the tourism marketing service model based on web2.0 when analyzing tourism enterprises.…”
Section: E Relationship Between Tourism Marketing and Newmentioning
confidence: 99%
“…From a managerial viewpoint, it was found that studies under this theme also related to the red, ‘strategy’ cluster, and explored opportunities for wineries to bolster their business tourism-related marketing strategies, such as enhancing the experiential aspect of their wine tourism offers and focusing on diaspora marketing [ 144 , 222 ]. In addition, emphasis was placed on the role of wine cellars as cultural attractions in rural tourism development [ 223 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figueiredo et al [ 11 ] attempted to elucidate the connection between food tourism and the countryside by exploring 73 relevant pieces of literature, revealing some potentially benign links between tourism, food, and the countryside, and identifying a direction for the development of rural food tourism. Bowen [ 12 ], through an online survey of 169 food producers, found that diaspora tourism can influence the development of food tourism in two aspects: participation in the diaspora network and the reverse diaspora effect, which effectively promotes the participation of local businesses and enhances food tourism and cultural value. Andrinos et al [ 13 ] applied SEM to reveal the extent to which environmental aesthetics, emotion, experience engagement, price, and authenticity influence tourists in food tourism activities.…”
Section: Literature Reviewmentioning
confidence: 99%